Students’ learning experiences in the Communication Program from a university in the Philippines - Sunliegh Camay Gador; Rowanne Marie Maxilom Mangompit; Joseleanor Melliza Magno (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study analyzed the students’ learning experiences in the Communication Program from a university in the Philippines. A descriptive method was used in analyzing the data gathered from the researcher-made questionnaires and exit interviews of the perceived fourth year student-respondents. Using categories of students’ learning experiences, findings revealed that experiential learning and social climate contribute mostly to their best and worst experiences in the university. Furthermore, aside from problem solving and application of theories into practice, quality of lectures, and discussion, three themes surfaced particularly related to the self, faculty, and university. As learners are encouraged to actively participate in the teaching-learning process and continue to make sense of their identity in a learning environment, the higher education institutions also have equal responsibilities of providing conditions that are conducive to achieving target learning outcomes. Such conditions comprise the schools’ facilities and information technology infrastructure, and carefully designed instructional packages including quality instructional materials and competent teachers. This study provides recommendations in redesigning the Communication Program based on the students' learning experiences.